2022
DOI: 10.5194/egusphere-2022-681
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Modeling the Influence of Chain Length on SOA Formation via Multiphase Reactions of Alkanes

Abstract: Abstract. Secondary Organic Aerosol (SOA) from diesel fuel is known to be significantly sourced from the atmospheric oxidation of aliphatic hydrocarbons. In this study, the formation of linear-alkane SOA was predicted using the Unified Partitioning Aerosol Phase Reaction (UNIPAR) model that simulated multiphase reactions of hydrocarbons. In the model, the formation of oxygenated products from the photooxidation of linear alkanes was simulated using a near-explicit gas kinetic mechanism. Autoxidation paths inte… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(5 citation statements)
references
References 32 publications
0
5
0
Order By: Relevance
“…For example, chamber studies showed that aromatic SOA yields increased with decreasing the NOx level within the NOx-rich region (Yang et al, 2020). A 415 gradual increase in alkane SOA was reported in the recent chamber study by Madhu et al (2022) with decreasing the NOx level over both NOx-rich and NOx-poor regions. The reduction of NOx in the NOx-rich region dramatically decreases nighttime biogenic SOA yields owing to the reaction of biogenic HCs with decreased nitrate radicals, but the reduced NOx increases daytime biogenic SOA yields (Han and Jang, 2023).…”
Section: Atmospheric Implications and Uncertaintiesmentioning
confidence: 82%
See 4 more Smart Citations
“…For example, chamber studies showed that aromatic SOA yields increased with decreasing the NOx level within the NOx-rich region (Yang et al, 2020). A 415 gradual increase in alkane SOA was reported in the recent chamber study by Madhu et al (2022) with decreasing the NOx level over both NOx-rich and NOx-poor regions. The reduction of NOx in the NOx-rich region dramatically decreases nighttime biogenic SOA yields owing to the reaction of biogenic HCs with decreased nitrate radicals, but the reduced NOx increases daytime biogenic SOA yields (Han and Jang, 2023).…”
Section: Atmospheric Implications and Uncertaintiesmentioning
confidence: 82%
“…The structure of the UNIPAR SOA model has been described previously (Cao and Jang, 2010;Im et al, 2014;Beardsley and Jang, 2016;Zhou et al, 2019;Yu et al, 2021c;Yu et al, 2022;Choi and Jang, 2022;Madhu et al, 2022;Han and Jang, 2023). Briefly, the key components of the UNIPAR model are described as follow:…”
Section: The Unipar Soa Modelmentioning
confidence: 99%
See 3 more Smart Citations